The Struggle Of The Islamic Da’wah Process In The Alcoholic Village: (Sociological-Historical Study of the Islamic Da’wah Process in the Village that Producing Alcoholic Drinking/arak in Poncol Hamlate, Kerek Village, Ngawi District, Ngawi District) - Untung Khoiruddin; Saiful Mujab; Burhanudin Syaifullah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This project involves discovering how da’wah Islam is moving, rejecting, and adapting in the society that produces traditional alcoholic drinking (ARJO/arak jowo) in Poncol-Kerek Village-Ngawi Regency. In the process of Islamic da'wah in Indonesia, especially Java, most of the auliya, ulama, and kyai run it with great patience, peace, and noble behavior, which then become the attraction of the community to follow it. The uniqueness of Islamic da'wah, characterized by politeness and morality in Indonesia, has become an exciting phenomenon that Muslims do not share in other regions, such as; the Middle East, India, Africa, etc. Furthermore, this research will explain in detail using historical and sociological analysis of the various challenges of da'wah in a village where the majority of the population is the producer of alcoholic drinks that are forbidden by the Islamic teaching. different rejection, acceptance, challenges faced by the kyai become a process of da'wah journey that is not easy. Eventually, this will be arranged based on observation, interview, and deep dialogue with the society there. The conclusions of this study are 1. The understanding of the community in Poncol hamlet as a society that produces alcoholic beverages (arak) is the majority of abangan groups that have minimal knowledge of Islam. In fact, at first, they distanced themselves from Islamic religious values ​​because they were seen as a threat to their economic activities. 2. Da'wah bil hikmah implemented by Islamic leaders there is very effective in changing the thinking of the local community. 3. pressure from the government and the police also significantly reduced the production of alcoholic beverages (arak) there.